2016
DOI: 10.4168/aair.2015.8.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Severity, and Treatment of Recurrent Wheezing During the First Year of Life: A Cross-Sectional Study of 12,405 Latin American Infants

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Purpose: This study aimed to determine the prevalence and severity of recurrent wheezing (RW) defined as ≥3 episodes of wheezing, risk factors, and treatments prescribed during the first year of life in Latin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
1
3
0
3
Order By: Relevance
“…The access to such a large medical database provides us with a rich source of information and reveals that the frequency of asthma‐like symptoms in infants and toddlers is high. Over a third of all infants fulfilled GINA criteria for asthma‐like symptoms, similar to the Tucson and Bisgaard studies, but double that in two recent real‐world epidemiological studies . However, only a small minority received controller therapy, even using permissive criteria of 50% of the recommended dose to define controller user.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The access to such a large medical database provides us with a rich source of information and reveals that the frequency of asthma‐like symptoms in infants and toddlers is high. Over a third of all infants fulfilled GINA criteria for asthma‐like symptoms, similar to the Tucson and Bisgaard studies, but double that in two recent real‐world epidemiological studies . However, only a small minority received controller therapy, even using permissive criteria of 50% of the recommended dose to define controller user.…”
Section: Discussionsupporting
confidence: 66%
“…Low SES was associated with a higher prevalence of wheezing in infants but controller therapy was less prevalent within the Orthodox Jewish and Arab populations who tend to have a lower SES as well as larger families and more crowded living conditions . The Latino studies of wheezing infants found that a low household income per month was associated with a higher prevalence of recurrent wheezing and severity markers whereas others showed only a slight effect of SES on wheezing in young children and no effect in adolescents in Canada …”
Section: Discussionmentioning
confidence: 99%
“…We showed that the prevalence of wheeze in early infancy (age < 4 months) is 7.7%, which is almost the same proportion (7.9%) of infants with recurrent wheezing who developed wheezes before the age of 3 months in reports from South America 14 . Although several studies have shown the prevalence of wheeze in infants (age < 12 months) as 37–56%, 1–3 about 20% of the infants developed wheeze within 4 months of age.…”
Section: Discussionmentioning
confidence: 57%
“…Although some studies have shown the prevalence and associated factors of wheeze in infants up to 1 year of age in some countries 1–3 or internationally, 4,14 no study has yet described the prevalence and associated factors of wheeze in early infancy (defined as age < 4 months), which is a risk factor for recurrent wheezing 13 ). Therefore, this population‐based, cross‐sectional study aimed to describe the prevalence of wheeze during early infancy and to ascertain factors associated with wheeze as part of a long‐term plan to identify potentially feasible interventions for prevention of wheeze.…”
mentioning
confidence: 99%
“…Estudo recente demonstrou prevalência de DA semelhante em lactentes sibilantes recorrentes (16,8%) e em não sibilantes (16,6%) e não encontrou associação entre o diagnóstico de dermatite atópica e sibilância recorrente no primeiro ano de vida. 22 No presente estudo, a prevalência de DA foi de 10,1% nos sibilantes recorrente e de 7,5% nos não sibilantes. A prevalência de dermatite atópica na família foi 11,5% e esta foi identificada como fator de risco independente para sibilância recorrente grave.…”
Section: Discussionunclassified